COCONUT MITE, (Aceria guerreronis, Keifer) – Bibliography - Ponniah Rethinam; Muhartoyo (International Coconut Community Journal, 2003)
Coconut mite, Aceria guerreronis, Keifer, which made its first appearance as pest in Mexico in 1965 as reported by Keifer, has spread far and wide. Now that 37 years have passed. Research efforts have been made on various aspects of this pest like, origin, occurrence, dispersal, symptoms, population dynamics, management practices like chemical control, bio control, cultural practices, varietal resistance/ tolerances, natural enemies, phytosanitary efforts etc. Two international seminars/ workshops have been held. Many group discussions, steering committee meetings, etc. were also held. Lots of publications have come. An earnest attempt has been made to collect the available literature on this pest which can benefit the member countries and others to know what has been done and what directions one has to move for future research and development. However, this bibliography is not the completed one. There may be many more and we will update as and when we get access to those references. We are confident that this bibliography will help to avoid duplication and take up need based research and development on Eriophyid mite.